Ethical IT innovation : a value-based system design approach - Spiekermann, Sarah (CRC Press is an imprint of the Taylor & Francis Group, an informa business, 2016)
Explaining how ubiquitous computing is rapidly changing our private and professional lives, this book stands at the intersection of computer science, philosophy, and management and integrates theories and frameworks from all three domains. It explores the latest thinking on computer ethics, including the normative ethical theories currently shaping the debate over the good and bad consequences of technology. It begins by making the case as to why IT professionals, managers, and engineers must consider the ethical issues when designing IT systems, and then uses a recognized system development process model as the structural baseline for subsequent chapters. It presents an extensive case study that applies the "Ethical SDLC" to the example of privacy protection in RFID enabled environments; explains how privacy can be built into systems; illustrates how ethical decisions can be consciously made at each stage of development. --